2009
DOI: 10.1161/circulationaha.108.797035
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Prolonged QT Interval and Their Contribution to Sudden Death Risk in Coronary Artery Disease

Abstract: Background-In a recent cohort study, prolongation of the corrected QT interval (QTc) was associated with an independent increased risk of sudden cardiac death (SCD). We evaluated determinants of prolonged QTc and the relationship of prolonged QTc to SCD risk among patients with coronary artery disease in the general population. Methods and Results-A case-control design was used. Cases were SCD patients with coronary artery disease among a metropolitan area of 1 000 000 residents (2002 to 2006); controls were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
186
1
17

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(219 citation statements)
references
References 36 publications
15
186
1
17
Order By: Relevance
“…More importantly, ECG data obtained from radiotelemetry recording demonstrated that in vivo transfection of Ca v 2.2‐α shRNA into AVG neurons not only increased the QT interval, QTc interval, QTd, QTcd, and Tpe but also induced a spontaneous ventricular tachyarrhythmia in conscious rats (Figures 6 and 7). It has been found that prolongation of the QT and QTc intervals, increase of the QTd and QTcd (a marker of spatial heterogeneity of ventricular repolarization), and prolonged Tpe (a marker of transmural dispersion of ventricular repolarization) are associated with increased risk of malignant ventricular arrhythmias and sudden cardiac death 49, 50, 51, 52. The results in the present study provide direct evidence that blunted ventricular vagal activity increases the susceptibility to ventricular arrhythmias and induces ventricular arrhythmias.…”
Section: Discussionsupporting
confidence: 63%
“…More importantly, ECG data obtained from radiotelemetry recording demonstrated that in vivo transfection of Ca v 2.2‐α shRNA into AVG neurons not only increased the QT interval, QTc interval, QTd, QTcd, and Tpe but also induced a spontaneous ventricular tachyarrhythmia in conscious rats (Figures 6 and 7). It has been found that prolongation of the QT and QTc intervals, increase of the QTd and QTcd (a marker of spatial heterogeneity of ventricular repolarization), and prolonged Tpe (a marker of transmural dispersion of ventricular repolarization) are associated with increased risk of malignant ventricular arrhythmias and sudden cardiac death 49, 50, 51, 52. The results in the present study provide direct evidence that blunted ventricular vagal activity increases the susceptibility to ventricular arrhythmias and induces ventricular arrhythmias.…”
Section: Discussionsupporting
confidence: 63%
“…Whether QTc contributes to increased hospital mortality in those with delirium is unknown 34. Prolonged QT interval is known to predict mortality in a variety of other conditions that are frequently encountered in the AMU such as: coronary artery disease,35 heart failure36 and diabetes mellitus 37, 38. Survival curves of those with/without prolonged QTc separated well within 50 days of admission, in a hospital‐wide study 7.…”
Section: Discussionmentioning
confidence: 99%
“…Longer QTc is well known to be independently associated with SCD in men and women 6, 22. In the case‐control Oregon Sudden Unexpected Death Study of patients with CAD (40% women), QTc was longer in those with SCD compared with controls (450±45 versus 433±37 ms, P <0.0001), and abnormally prolonged QTc was associated with a 5‐fold increased risk of SCD 23. In our study, women with SCD had a mean QTc of 446±27 ms.…”
Section: Discussionmentioning
confidence: 99%